2007
DOI: 10.1161/atvbaha.107.155762
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Reduces Glucose-Induced Oxidative Stress Mediated by NAD(P)H Oxidase via AMPK-Dependent Mechanism

Abstract: Objective-Hyperglycemia is the main determinant of long-term diabetic complications, mainly through induction of oxidative stress. NAD(P)H oxidase is a major source of glucose-induced oxidative stress. In this study, we tested the hypothesis that rosiglitazone (RSG) is able to quench oxidative stress initiated by high glucose through prevention of NAD(P)H oxidase activation. Methods and Results-Intracellular ROS were measured using the fluoroprobe TEMPO-9-AC in HUVECs exposed to control (5 mmol/L) and moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
162
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(176 citation statements)
references
References 46 publications
11
162
2
1
Order By: Relevance
“…However, the precise mechanism by which AMPK protects the endothelium from oxidative stress remains unclear. Ceolotto et al (41) reported that AMPK protects HUVEC against glucose-induced oxidative stress by suppressing hyperactivity of NAD(P)H oxidase. Deng et al (42) reported that AMPK protects human aortic endothelium by increasing NO production via endothelial NOS phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise mechanism by which AMPK protects the endothelium from oxidative stress remains unclear. Ceolotto et al (41) reported that AMPK protects HUVEC against glucose-induced oxidative stress by suppressing hyperactivity of NAD(P)H oxidase. Deng et al (42) reported that AMPK protects human aortic endothelium by increasing NO production via endothelial NOS phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Ces auteurs ont rapporté une réduction significative de la capacité de ces animaux à féconder en raison d'une asthénozoospermie (défaut de mobilité) et d'un taux important d'anomalies morphologiques (fragilité membranaire de la tête, anomalies des mitochondries) des spermatozoïdes. Toutefois, aucune altération de la morphologie des testicules ou de la production de sperme n'a la réactivation de la kinase pourrait ainsi contrecarrer les effets négatifs du stress oxydatif lié à cette maladie métabolique [35]. Dans un modèle murin de diabète de type II, un activateur de l'AMPK, le resvératrol, permet en effet de diminuer la production d'anion superoxyde et la carbonylation 7 des protéines par un mécanisme qui dépend de la kinase [36].…”
Section: Rôle De L'ampk Dans Les Fonctions Des Spermatozoïdesunclassified
“…19) RSG also protects endothelial cells from glucose-induced oxidative stress through an AMPActivated Protein Kinase-dependent molecular pathway. 20) In addition, PPAR agonist reduces the fraction of neonatal rat CMCs (rCMCs) that undergo apoptosis under oxidative stress, through upregulation of Bcl-2 expression. 21) Given this background, we hypothesized that PPAR agonist RSG can reduce the apoptosis of rCMCs in the oxidative state created by H 2 O 2 , and that this protective action results from TRx overexpression.…”
mentioning
confidence: 99%